„ICH FORDRE SO VIEL FREIHEIT UND MUSSE, ALS NÖTIG IST, ÜBER MICH SELBST, ÜBER MEINE BESTIMMUNG UND MEINEN WERTH ALS MENSCH ZU DENKEN“.1 ZUR KUNST- UND FREIHEITSKONZEPTION BEI KARL PHILIPP MORITZ - Tkaczyk, Krzysztof (Literatūra, 2016)
In 1786 in Rome, Johann Wolfgang Goethe wrote about him: “He is my younger brother; we art cut from the same mould. However, fate was against him, whereas I was fortune’s favourite.” He meant Karl Phillip Moritz (1756-1793), a German writer and art critic, Greek mythology historian, precursor of modern psychology and the author of psychological novel. If we assume that Goethe’s comments concern Moritz’s material and social status only, we would have to admit that Goethe was right. However, if we apply these judgments to the quality of his (Moritz’s) works, we would be inclined to saying that in this case the great Goethe was wrong. In his aesthetic, Moritz is far more interesting and progressive than his “elder brother”; in his literary criticism – more consistent than Schiller, and in perceiving society and politics – more radical than Kant. This article is mainly on key concept regarding Moritz’s aesthetic works: the concept of beauty and its functionalism. Definition of “the work of art” as a closed, specified unity enables Moritz to get out of the frame of aesthetics itself and to enter the sphere of politics. Moritz liberates man from the restraints of utility and treats him as a noble individual who possesses the artistic value in himself.